Cognitive dysfunction in hypertension (BioMedical Research in Medicine (BMR Medicine) (ISSN 2349-0756), 2024)
The objectives of the study is; cognitive dysfunctions between the essential hypertensive. 50 hypertensives were taken for the study, assessed and analyzed. The samples were matched for age, sex, education and socio-economic status. The tools used were socio-demographic data and clinical proforma, SMMSE (Standardized Mini Mental Status Examination) scale and BCRS (Brief Cognitive Rating Scale). They’re very significant cognitive deficits measured by SMMSE on orientation and constructional ability and in BCRS it was in orientation only. The overall cognitive decline on both SMMSE and BCRS scores were very highly significant, thus signifying a global cognitive decline.